Sensory Processing: Advances in Understanding Structure and Function of Pitch-Shifted Auditory Feedback in Voice Control - Charles R Larson; Donald A Robin (AIMS Neuroscience, 2016)
The pitch-shift paradigm has become a widely used method for studying the role of voice pitch auditory feedback in voice control. This paradigm introduces small, brief pitch shifts in voice auditory feedback to vocalizing subjects. The perturbations trigger a reflexive mechanism that counteracts the change in pitch. The underlying mechanisms of the vocal responses are thought to reflect a negative feedback control system that is similar to constructs developed to explain other forms of motor control. Another use of this technique requires subjects to voluntarily change the pitch of their voice when they hear a pitch shift stimulus. Under these conditions, short latency responses are produced that change voice pitch to match that of the stimulus. The pitch-shift technique has been used with magnetoencephalography (MEG) and electroencephalography (EEG) recordings, and has shown that at vocal onset there is normally a suppression of neural activity related to vocalization. However, if a pitch-shift is also presented at voice onset, there is a cancellation of this suppression, which has been interpreted to mean that one way in which a person distinguishes self-vocalization from vocalization of others is by a comparison of the intended voice and the actual voice. Studies of the pitch shift reflex in the fMRI environment show that the superior temporal gyrus (STG) plays an important role in the process of controlling voice F0 based on auditory feedback. Additional studies using fMRI for effective connectivity modeling show that the left and right STG play critical roles in correcting for an error in voice production. While both the left and right STG are involved in this process, a feedback loop develops between left and right STG during perturbations, in which the left to right connection becomes stronger, and a new negative right to left connection emerges along with the emergence of other feedback loops within the cortical network tested.